GEOSEMIOTICS IN BALI LINGUISTIC LANDSCAPE: DISSECTING THE INTENDED MEANINGS OF THE SHOPFRONT SIGNAGES - Riskia Setiarini; Dewianti Khazanah; Hadi Sampurna; Syamsul Anam (UIN Raden Mas Said Surakarta, 2024)
This article investigates salient components in Bali shopfront signages to discover the intended meanings behind the use of the signs and the use of English and its counterparts, in particular local/national languages, in them. Two approaches employed are geosemiotics–to construe the meanings of the signs–and linguistic landscape–to reveal the role of English and its counterparts in them. Bali, specifically Kuta was selected as the most affluent tourism area and is chosen due to the fact that it experiences the apparent change in its linguistic landscape. The former approach covers three prominent elements, such as interaction order, visual semiotics, and place semiotics, conceiving the whole message the sign makers convey. Meanwhile, the latter focuses on the revelation of the visibility of English and the local and national languages in the signages and the revelation of their implied meaning. The collected data are 10 signages, as these are most representative data to select, in terms of the outright blends of English and its counterparts. The result of the analysis indicates some facts conceiving interaction, visual and situational meanings. English was mostly found in the type of businesses, the offers and products, and slogan. The visibility of English along with local/national languages and their influence in all selected data indicates modernity, efficiency and effectiveness, luxury, being communicative, non-traditional manner, and happy-go-lucky sense. The Indonesian and local languages are reported to be used as the names of the shop, and as referring to either low-budget or affordable prices of products or culturally/locally bound reason.